Taking advantage of sulfur impurities present in commercial carbon nanofibers to generate selective palladium catalysts. (February 2020) - Morales, M.V.; Guerrero-Ruiz, A.; Castillejos, E.; Asedegbega-Nieto, E.; Rodríguez-Ramos, I.
Abstract: Achieving high selectivity is one of the major challenges in heterogeneous catalysis, being carbon materials universally employed as catalysts support due to their so-called "inert" nature. However, due to the complexity of its intrinsic characteristics, there are still several factors to bear in mind when selecting the appropriate carbon support. In this work we demonstrate that the remaining sulfur impurities in one type of commercial carbon nanofibers (CNFs) drastically alter the catalytic properties of palladium by triggering electro-deficient active sites. Two as-received CNFs thermally processed at different severity degrees, namely PS and HHT, were used to support Pd nanoparticles through the wet impregnation technique using palladium nitrate as precursor. The proof of principle is demonstrated through two transformation reactions of biomass platform molecules: the hydrogenation of 5-hydroxymethylfurfural, performed in a batch-type reactor, and the ethanol dehydrogenation/decarbonylation reaction, carried out in a continuous flow fixed-bed reactor. In both reactions, Pd/PS was substantially more selective than its sulfur-free counterpart Pd/HHT, and one of the most selective in comparison with the state-of-the-art Pd catalysts. This finding makes available a simple, easy and green strategy to design carbon-supported Pd catalysts for selective hydrogenation and dehydrogenation reactions. Graphical abstract: Image 1